TETIKESAN PRACTICAL TRAINING OF WAYANG PARWA BEBADUNGAN STYLE PERFORMANCE IN SANGGAR MAJALANGU - Marajaya, I Made; Marhaeni, Ni Komang Sekar; Suteja, I Kt. (Institut Seni Indonesia Denpasar, 2024)
Abstract Wayang Parwa performances in the last three decades have become increasingly rare in society. This performance originates from the Mahabharata epic and is accompanied by the Gender Wayang gamelan, which is one of the oldest in Bali. Wayang Parwa is usually used as a basis for learning to become a puppeteer in formal and non-formal education. Wayang Parwa has many versions, and in Bali, there are four styles of Wayang Parwa: Bebadungan Style, Sukawati Style, Tunjung Style, and Buleleng (North Bali). One of the styles with the most favorite is the Bebadungan style, which is spread across six districts/cities in Bali, such as Tabanan, Negara, Klungkung, Bangli, Karangasem, and Denpasar City. With the emergence of various variants of innovative wayang performances, the popularity of Wayang Parwa has decreased. To maintain the existence of the Wayang Parwa Bebadungan Style performance in this millennial era, conservative efforts needed to be made, namely through training. Considering the Wayang Parwa Bebadungan style performances by today's young puppeteers, many need to be stronger in Tetikesan (puppet movements). For this reason, the training material provided to members of Sanggar Majalangu, Kerobokan Village, North Kuta District, Badung Regency, led by I Made Agus Adi Santika, is Tetikesan. This training could answer the public's opinion that the weakness of the Wayang Parwa Bebadungan style performance refers to Tetikesan. The training was focused on one of the studio members using instructional, structured, gradual, and innovative learning methods by utilizing YouTube media, which releases audio recordings of Wayang Buduk performances by puppeteer Ida Bagus Arnawa (deceased) and his son, puppeteer Ida Bagus Puja (deceased) as standardization of the Bebadungan style. Keywords: Training, Tetikesan, Wayang Parwa Bebadungan Style